A Resolução de problemas por meio do uso de jogo no ensino de matemática nos anos iniciais - Varlesse, Ananda de Oliveira [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
This work aims to analyze inductive and deductive reasoning skills through a game called Game of Circles. For this, a qualitative research was carried out with the participation of 25 students enrolled in the fifth year of a municipal school in the city of Cruzeiro. To guide this research, the following question was elaborated: What contribution to Problem Solving through the use of games will produce in the development of the inductive and deductive reasoning of students of the 5th year of the Initial Years?. In this research three meetings were held in which the Game of Circles was applied in three different ways, using Problem Resolution techniques. For data collection, audio records were made as well as written records. According to the National Curriculum Parameters, a mathematical problem is a situation that demands the accomplishment of a sequence of actions or operations to obtain a result, that is, the solution is not available at the beginning, however it is possible to construct it. In the process of data analysis, the interest generated in the students by the game and the posture they maintained throughout the work, mobilizing their knowledge in front of the proposed problem, stands out

Este trabalho tem por objetivo analisar habilidades de raciocínio indutivo e dedutivo através de um jogo intitulado Jogo dos Círculos. Para tanto foi realizada uma pesquisa de cunho qualitativo desenvolvida com a participação de 25 alunos, matriculados no quinto ano de uma escola municipal da cidade de Cruzeiro. Para nortear esta pesquisa, foi elaborada a seguinte questão: Qual contribuição a Resolução de Problemas através do uso de jogos irá produzir no desenvolvimento do raciocínio indutivo e dedutivo de alunos do 5º ano dos Anos Iniciais?. Nesta pesquisa foram realizados três encontros no qual foi aplicado o Jogo dos Círculos de três formas diferentes, por meio de técnicas de Resoluções de Problemas. Para a coleta de dados foram feitos registros em áudio, assim como registros escritos. Segundo os Parâmetros Curriculares Nacionais, um problema matemático é uma situação que demanda a realização de uma sequência de ações ou operações para obter um resultado, ou seja, a solução não está disponível de início, no entanto é possível construí-la. No processo de análise dos dados destaca-se o interesse gerado nos alunos pelo jogo e a postura que mantiveram ao longo do trabalho, mobilizando seus conhecimentos frente ao problema proposto
Solving problems through the use of play in teaching mathematics in the early years
Keywords: Matemática - Estudo e ensino; Jogos em educação matematica; Raciocínio; Mathematics Study and teaching